Penyebab Perbedaan Hasil Perhitungan Jadwal Waktu Salat di Sumatera Utara - Muhammad Hidayat (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2018)
A fact that there are many prayer times schedules that are used by the community with each other different contents. Among these schedules there are mentioned sources of extraction or constituents but many are not mentioned. One schedule with another schedule is different from 2 or 3 minutes, even more than that can reach tens of minutes. In this study, it was explained that the differences in the results of the calculation of prayer time schedules in North Sumatra were caused by several factors including differences in data used such as: coordinates, sun declination, equation of time, solar height, energy and factors caused by regional time correction, such as differences between Prayer time schedule in Labuhan Batu Selatan regency is calculated using the location of the place, with the prayer time schedule in Labusel Regency counted using Regional Time Correction with Medan City markaz (-5 minutes).Keywords: Differences, Prayer Times.